Practical Application of ±250‐kV DC‐XLPE Cable for Hokkaido–Honshu HVDC Link. Issue 3 (May 2015) - Watanabe, Chizuo; Itou, Yasuo; Sasaki, Hidetaka; Murata, Yoshinao; Suizu, Makoto; Sakamaki, Masatoshi; Watanabe, Masaru; Katakai, Shoshi
SUMMARY The long‐term dc properties of DC‐XLPE insulation materials, which have been developed for dc use, were investigated. It was found that the lifetime of DC‐XLPE under dc voltage application is extended by the addition of nano‐sized filler. The time dependence of the space charge distribution at 50 kV/mm was observed for 7 days. Almost no accumulation of space charge in DC‐XLPE was found. The 250‐kV DC‐XLPE cables and accessories were manufactured and subjected to a type test and PQ test for use in the Hokkaido–Honshu dc link facility owned by the Electric Power Development Co., Ltd. These tests were performed under conditions that included a polarity reversal test for line commutated converter (LCC) systems as recommended in CIGRE TB 219. The test temperature was 90 °C. The type test and PQ test were successfully completed. The DC‐XLPE cable and accessories were installed in summer 2012 for the Hokkaido–Honshu dc link. After the installation of the dc extruded cable system, a dc high‐voltage test at 362.5 kV (=1.45 PU) for 15 min was successfully completed in accordance with CIGRE TB 219. This dc extruded cable system was put into operation in December 2012 as the world's highest‐voltage extruded dc cable in service and the world's first dc extruded cable for a LCC system including polarity reversal operation.